PEMIKIRAN MUHAMMAD NATSIR TENTANG PERTAUTAN AGAMA DENGAN NEGARA - Muhaemin Muhaemin (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2015)
This article examines the thinking of Muhammad Natsir of religion and state. The aim of this study is to describe descriptively about Muhammad Natsir view the relation between religion and state in the context of Indonesia. The research method used in this research is the study of literature by searching texts relating to Muhammad Natsir and religion and the state. The sources referenced text not only from the writings directly from Muhammad Natsir are referred to as primary sources but also refers to the intellectual outlook of Muhammad Natsir which is also known as a secondary source. This study came to the conclusion that Muhammad Natsir is the figure of the intellectual and activist Indonesia in the 19th century which has been struggling for unification between religion and state in the context of Indonesia. Religion and state are two entities that should not be separated. Religion has taught widely to the public how good state. Religion loading concepts clear rule that can be used as a reference in managing government. For him the unification of religion and state is a fixed price, but do not have to do with violent means. He did not agree with the ways DI fighting Islam by means of rebellion against authority. For him, Islam is shown in the concept of the ideal state to bring peace, love not the face of violence.